Kedudukan Hukum Pria Yang Melakukan Perkawinan Nyentana Sebagai Ahli Waris Dalam Hukum Waris Adat Masyarakat Bali (Studi Putusan Mahkamah Agung Nomor 2991K/PDT/2015) - Shirley Shirley; Rosnidar Sembiring; Idha Apriliyana; Yefrizawati Yefrizawati (Iuris Studia: Jurnal Kajian Hukum, 2022)
The Balinese traditional community adheres to a patrilineal kinship system, which is a kinship system that draws lineage from the father's side. However, it becomes a problem when a family only has daughters as successors, so they have to do a nyentana marriage with a man who agrees that his status will change to pradana when doing a nyentana marriage with a woman whose status is elevated to sentana rajeg. Similar to the Patrilineal system in general, in terms of inheritance, the customary law of the Balinese customary community stipulates that only boys are entitled to inherit and will cover the rights of girls as beneficiaries of their parents. Based on this, the problems raised in this thesis research are how the nyentana marriage system is in Balinese traditional society, how is the legal position of men who carry out nyentana marriages as heirs in Balinese customary inheritance law, how is the legal analysis of the judge's decision in the Supreme Court Decision Number 2991K /PDT.2015. This research is descriptive analytical with the approach used is normative juridical. The data collected is then processed and analyzed qualitatively, using an inductive method to draw a conclusion. The position of a man who performs a nyentana marriage with a woman sentana rajeg is that he must leave the kinship line of his biological father, so that all relations with his family of origin are cut off, including the rights that he originally obtained as an heir on the basis of the consideration that he is considered to have left his ancestors and obligations so that he only has the right to inherit with the wife's family and is responsible in the customary community where the wife's family comes from.